مراقبة استجابة مجموعات الأرز اللبناني Cedrus libani A. Richard الطبيعية في سورية للمتغيرات المناخية باستخدام الصور الفضائية MODIS NDVI - قبيلي عماد; ثابت علي; إبراهيم عبير (Latakia University Journal -Biological Sciences Series, 2016)
حللت الدراسة التباين الزمني للصور الفضائية MODIS NDVIلمجموعات الأرز اللبناني الطبيعية في القسم الشمالي الرطب من سلسلة الجبال الساحلية السورية على سفحها الشرقي (صلنفة، جوبة برغال)، و علاقتها مع المتغيرات المناخية (درجة الحرارة، الهطول المطري) خلال الفترة 2004-2014. اُختبر التباين في قيم مؤشر الاختلاف النباتي القياسي (NDVI) السنوية و الفصلية لمجموعات الأرز، و التأثير التراكمي للمتغيرات المناخية (درجة الحرارة، الهطول المطري) في هذه المجموعات الحرجية باستخدام علاقات الانحدار الخطي البسيط (Simple Linear Regression) ومعامل الارتباط ((Pearson. أظهرت قيم اﻟ NDVI لمجموعات الأرز اللبناني تزايداً معنوياً في صلنفة و جوبة برغال (0.006، 0.004 / سنة) على التوالي. وجد إن قيم اﻟ NDVI السنوية ترتبط معنوياً مع المعدل السنوي للأمطار في جوبة برغال (R= 0.689). كما لوحظ اتجاهاً معنوياً نحو التزايد في قيم اﻟ NDVI الفصلية في صيف صلنفة و شتاء جوبة برغال(R= 0.638, R= 0.724) على التوالي. أظهرت النتائج وجود تأثير تراكمي لدرجة الحرارة في الأرز اللبناني في صلنفة و جوبة برغال في الخريف و الشتاء، في حين لوحظ التأثير التراكمي للأمطار في الخريف و الصيف. This study was analyzed the temporal variation of Moderate Resolution Imaging Spectroradiometer (MODIS) Normalized Difference Vegetation Index (NDVI) of natural stands of cedrus libani in the northern humid part and eastern exposure of the Syrian coastal mountains (Slenfeh, Jawbat Burghal), and its correlation with climatic variables (temperature and precipitation) during the period of 2004-2014. We examined the interannual and seasonal variation in NDVI values of Cedrus stands, and accumulative effects of climatic variables (temperature and precipitation) on stands using simple linear regression and correlation (Pearson). The NDVI values of Cedrus libani stands showed signiﬁcant increase in Slenfeh and Jawbat Burghal (0.006, 0.004 /year) respectively. We found that the annual mean NDVI was signiﬁcantly correlated with annual mean precipitation in Jawbat Burghal (R = 0.689).The signiﬁcant increase trend of seasonal mean NDVI was in Slenfeh summer and Jawbat Burghal winter (R = 0.638, R = 0.724) respectively. The results showed, there were accumulative effects of temperature on Cedrus libani in Slenfeh and Jawbat Burghal in autumn and winter, while the accumulative effects of precipitation in autumn and summer were noted.